The Oxford handbook of Daniel Defoe - Seager, Nicholas ca. 20./21. Jh; Downie, James A. 1951- (Oxford University Press, 2023)
"The Oxford Handbook of Daniel Defoe is the most comprehensive overview available of the author's life, times, writings, and reception. Daniel Defoe (1660-1731) is a major author in world literature, renowned for a succession of novels including Robinson Crusoe, Moll Flanders, and A Journal of the Plague Year, but more famous in his lifetime as a poet, journalist, and political agent. Across his vast oeuvre, which includes books, pamphlets, and periodicals, Defoe commented on virtually every development and issue of his lifetime, a turbulent and transformative period in British and global history. Defoe has proven challenging to position—in some respects he is a traditional and conservative thinker, but in other ways he is a progressive and innovative writer. He therefore benefits from the range of critical appraisals offered in this Handbook. The Handbook ranges from concerns of gender, class, and race to those of politics, religion, and economics. In accessible but learned chapters, contributors explore salient contexts in ways that show how they overlap and intersect, such as in chapters on science, environment, and empire. The Handbook provides both a thorough introduction to Defoe and to early eighteenth-century society, culture, and literature more broadly. Thirty-six chapters by leading literary scholars and historians explore the various genres in which Defoe wrote; the sociocultural contexts that inform his works; his writings on different locales, from the local to the global; and the posthumous reception and creative responses to his works."
Keywords: Defoe, Daniel -- 1660-1731; Aufsatzsammlung